Art and politics now - Downey, Anthony (London : Thames and Hudson, 2014)
This book is a richly illustrated survey of more than 200 artists whose works address the political, often using radical approaches and techniques to communicate their ideas. Since the turn of the 21st century, contemporary artists have increasingly engaged with some of the most pressing issues facing our world and their art has taken a distinctly political turn. Eleven themed chapters with integrated illustrations each provide a closely woven argument about the contribution of specific artworks and projects to different aspects of political and social engagement, from globalization and citizenship to activism and the environment.
Introduction: Global culture and political engagement -- Globalization: Worldwide trade and uneven development -- Labour: Human capital and the work of art -- Citizens: Global refugees and the logic of exculsion -- Activism: The politics of non-engagement -- Conflict: State power and states of emergency -- Terror: Terrorism, torture and the spectacle of images -- History: The future of re-visiting the past -- Camps: The politics of exception -- Environments: Ecologies of engagement -- Economies: Capital and its distribution -- Knowledge: Producing information in a globalized world.
Includes bibliographical references (pages 233-234) and index.
Text in English.
Keywords: 2000 - 2099; Art -- Political aspects -- 21st century; Art -- Political aspects; Politische Kunst